Structural, electronic and photovoltaic characterization of multiwalled carbon nanotubes grown directly on stainless steel - Camilli, Luca; Scarselli, Manuela; Gobbo, Silvano Del; Castrucci, Paola; Gautron, Eric; De Crescenzi, Maurizio (Beilstein Journal of Nanotechnology, 2012)
We have taken advantage of the native surface roughness and the iron content of AISI-316 stainless steel to grow multiwalled carbon nanotubes (MWCNTs) by chemical vapour deposition without the addition of an external catalyst. The structural and electronic properties of the synthesized carbon nanostructures have been investigated by a range of electron microscopy and spectroscopy techniques. The results show the good quality and the high graphitization degree of the synthesized MWCNTs. Through energy-loss spectroscopy we found that the electronic properties of these nanostructures are markedly different from those of highly oriented pyrolytic graphite (HOPG). Notably, a broadening of the π-plasmon peak in the case of MWCNTs is evident. In addition, a photocurrent was measured when MWCNTs were airbrushed onto a silicon substrate. External quantum efficiency (EQE) and photocurrent values were reported both in planar and in top-down geometry of the device. Marked differences in the line shapes and intensities were found for the two configurations, suggesting that two different mechanisms of photocurrent generation and charge collection are in operation. From this comparison, we are able to conclude that the silicon substrate plays an important role in the production of electron–hole pairs.
Keywords: carbon nanotubes; electronic properties; heterojunction; photovoltaic; stainless steel